NAIRU ESTIMATES IN A TRANSITIONAL ECONOMY WITH AN EXTREMELY HIGH UNEMPLOYMENT RATE: THE CASE OF THE REPUBLIC OF MACEDONIA - Trpeski, Predrag; Tevdovski, Dragan (Faculty of Economics, University of Belgrade, Serbia, 2015)
The main goal of the paper is to estimate the NAIRU for the Macedonian economy and to discuss the applicability of this indicator. The paper provides time-varying estimates for the period 1998-2012, which are obtained using the Ball and Mankiw (2002) approach, supplemented with the iterative procedure proposed by Ball (2009). The results reveal that the Macedonian NAIRU has ahumpshaped path. The estimation is based on both the LFS unemployment rate and the LFS unemployment rate corrected for employment in the grey economy. The dynamics of the estimated NAIRU stress the ability of the NAIRU to present the cyclical misbalances in a national economy
Keywords: NAIRU, unemployment, inflation, Macedonia